Internet connectivity disruption in Portugal (Portugal) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Portugal. Data sourced from IODA.
Network Disruption Incident ID: PT-2026-0007. Severity: critical. Confidence: 75%